Μουσικἠ como disciplina propedêutica da dialética na república-VII - Siqueira, Sávio Lima (2022)
We analyzed Μουσικἠ as a propaedeutic discipline of Dialectics, highlighting its mimetic role and its contribution as an educational activity in the preparation for Philosophy. We present a non-Pythagorean interpretation of Μουσικἠ in Plato. We highlight the projective interpretation of the Platonic dialogues, not carrying out a dogmatic interpretation. The philosopher starts from the sensitive to rise to the intelligible, in the context of analogies, whose purpose is to lead the listener / reader to contemplate what he cannot discern with the eyes and ears of the body. We evaluated the notion of Μουσικἠ that Plato presents in the Republic and its relevance to the exercise of Philosophy. The problem posed by the insertion of Μουσικἠ in the curriculum of studies defined in Book VII of the Republic presents two possibilities: either Μουσικἠ is at the apex of the studies of the philosopher-king, inserted in Dialectics, or must be included in the group of propaedeutic studies of Dialectics. We opted for this second alternative, for positive and negative reasons. The positive ones are based on the textual reference to Μουσικἠ in the text of the dialogue, from 521c onwards, as “discipline that elevates the soul of what is born to what it is”, even before beginning the curriculum of the other propaedeutic disciplines: Arithmetic (522c) , Geometry (526c), Astronomy (527d), Stereometry (528a), finally reflecting on “true Astronomy” (529a) and Harmony (530 c), before addressing the Dialectic (532b). We then approach the problem posed by the need to insert Μουσικἠ into the “Analogia da Linha” (VI 509d ad fin.), In close relationship with Dianoia. As for the negative reasons for associating Μουσικἠ with Dialétic, we point out the pedagogical impracticability of a “dialectic music”, of null educational scope, as a discipline of the superior noeta. We reinforce this argument by attributing to the Pythagoreans this conception of Μουσικἠ.